Simulating the Interconnected Eastern Mediterranean–Black Sea System on Climatic Timescales: A 30-Year Realistic Hindcast - Stamatios Petalas; Elina Tragou; Ioannis G. Mamoutos; Vassilis Zervakis (Journal of Marine Science and Engineering, 2022)
Inter-basin water exchanges can be quite important in climatic-scale numerical studies simulating the circulation and hydrographic characteristics of neighboring oceanic basins connected through narrow straits. The crucial role of the interaction between the Mediterranean and the Black Seas is often overseen in simulations, which rely mostly on parameterizations to describe the exchange, essentially decoupling the two basins. In this study, the fully interconnected Eastern Mediterranean–Black Sea system is simulated for the historical period (1985–2015) using realistic boundary conditions (lateral, atmospheric and hydrological), with a hydrodynamic fully three-dimensional ocean modeling system. The setup of such a configuration is thoroughly described and the performance of the 30-year hindcast product is validated exhaustively against observations and model results, by evaluating the representation of surface fields, circulation, three-dimensional hydrographic characteristics, volumetric water exchanges, and the spatio-temporal variability of the above. The comparison shows exceptional performance, minimal drift, and substantial improvement compared to modeling studies that do not include the interaction. Moreover, due to the free-run configuration of the simulation (i.e., absence of assimilation schemes) no additional input is required other than the respective boundary conditions, making it possible to reliably extend the same setup for scenarios where observational data are not available, such as in future projections.